2019
DOI: 10.3390/en12214159
|View full text |Cite
|
Sign up to set email alerts
|

System Perspective on Biogas Use for Transport and Electricity Production

Abstract: Linköping municipality has managed biogas driven buses in the regional transport system since 1997 and all buses in the municipality have run on biogas since 2015. Biogas is a renewable fuel and by replacing fossil fuels it can help to lower net CO2 emissions. However, Internal Combustion Engines (ICE) in buses still have a rather low effciency, in the range of 15–30%. If the combustion of biogas instead takes place in a combined cycle gas turbine (CCGT) effciency could be higher and heat losses reduced. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Hence, Germany is a leading country in this field [6]. Biogas can be utilized-after treatment-in numerous applications, like electricity and heat generation, connection to the natural gas grid, or as biofuel in vehicles [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Germany is a leading country in this field [6]. Biogas can be utilized-after treatment-in numerous applications, like electricity and heat generation, connection to the natural gas grid, or as biofuel in vehicles [7].…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation of IC engines to combustion of gaseous fuels may become a contemporary scientific trend as to the use of biogas [90][91][92]. Biogas obtained from the decomposition of, e.g., sewage [93], organic municipal waste [94,95], animal faeces [96], agricultural and food industry waste [97,98] and plant materials [96,97,99], can be used by plants processing these materials to propel their machinery and equipment [100,101]. Biogas is a mixture of gases characterized by a varied composition, but it can be purified to bio-methane and then meet the quality standards of natural gas [102].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of biogas have increased the adoption rate amongst many countries. Biogas for instance can be utilized after treatment in numerous applications such as provision of electricity and heat generation, connection to the natural gas grid, or as biofuel in vehicles [13]. Several studies on biogas technology potentials and their adoption in various developing countries have shown that biogas technology has high potential in developing countries as an alternative energy source [15][16][17].…”
Section: The Major Driving Factors In Adoption Of Biogas Technologymentioning
confidence: 99%